Female adolescent athletes' coping: A season-long investigation - Tamminen, K. A.; Holt, N. L. (Journal of Sports Sciences, 2010)
Athletes' stressors and coping have been studied over relatively short periods or time (i.e. 28 or 31 days; Nicholls, 2007), but little is known about how stressors and coping fluctuate over the course of an entire competitive season. The first objective of this study was to examine recurrent stressors and coping strategies over the course of the season. The second objective was to examine coping as a process. Thirteen female basketball players (mean age 16 years) completed pre- and post-season interviews and maintained audio diaries during the season. Content analyses were completed and themes were analysed longitudinally across three phases of the season (early, mid, and late). Reported stressors changed across phases of the season, and these changes appeared to relate to the team's changing contextual demands. Coping strategies also changed across phases of the season. Individual profiles of each athlete's coping over the season were created. Ten athletes were generally more reactive in their coping, while only three athletes were more proactive. The three athletes identified with a proactive approach planned their coping and used feedback to evaluate coping efforts. Planning and evaluation appeared to distinguish between more reactive and more proactive coping.